Pelatihan dan Pendampingan Penyusunan Pelaporan Keuangan Panti Asuhan Putri Aisiyah Kota Malang - Gina Harventy; Achmad Syaiful Hidayat Anwar (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2021)
This community service activity aims to provide training and assistance in the preparation of financial reports at the Putri Asisiyah Orphanage in Malang City. Putri Aisyiyah Orphanage is one of the Amal Usaha Muhammadiyah (AUM) in Malang. The training and assistance in the preparation of financial reports are related to the problems faced by the orphanage manager, namely the activity of recording and reporting on orphanages that have not been carried out in an orderly manner and in accordance with reporting standards. Putri Aisiyah Orphanage has a business unit that has experienced significant development until now, so it is necessary to record and prepare good financial reports for the orphanage. So that administrators can evaluate the performance of operational activities of the orphanage and catering business units. The method of implementing the service program consists of socializing the importance of preparing financial reporting, training and assistance in the preparation of financial reports. The results of this service activity, the management and financial administration section of the Putri Aisiyah Orphanage have the skills (expertise) in making / compiling excel-based computerized financial reports and this service program has achieved the output of computational computational financial reporting work excel at the Putri Aisiyah Orphanage.